2017
DOI: 10.18805/ijar.v0iof.9187
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of relationships between pork color and muscular texture traits for entrepreneurial decisions

Abstract: This study was done to examine correlation between pork color and texture traits for entrepreneurial decision-making. Most traits between both factors had significant correlations, but presented low correlation values. The first correlation in the results of canonical correlation analysis (CCA) maintained relatively high values of 47.9. The value was positive and negative contributions for hardness and gumminess, respectively. Loadings of color traits were more influenced by lightness and whiteness. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Lertpatarakomol et al (2019) also reported a lower L* (51.19) in (Large White x Landrace) x Duroc pigs than observed here, although they obtained a similar percentage of meat in the yellow spectrum b* (11.47) to that in our experiment (11.68). Kim et al (2019) recorded an average value of L* (48.60) in their experiment with the Berkshire breed. Table 2 shows the carcass value indicators in the hybrid (CLW x CL) x D pigs according to slaughter weight.…”
Section: Resultsmentioning
confidence: 98%
“…Lertpatarakomol et al (2019) also reported a lower L* (51.19) in (Large White x Landrace) x Duroc pigs than observed here, although they obtained a similar percentage of meat in the yellow spectrum b* (11.47) to that in our experiment (11.68). Kim et al (2019) recorded an average value of L* (48.60) in their experiment with the Berkshire breed. Table 2 shows the carcass value indicators in the hybrid (CLW x CL) x D pigs according to slaughter weight.…”
Section: Resultsmentioning
confidence: 98%
“…For this reason, color changes in the tissues of farm animals, viz. sheep, goat, cattle, swine, chicken, fish, etc., have been studied extensively (Boulianne and King, 1998;Bryne et al, 2000;Huidobro et al, 2003;Karabacak et al, 2012;Karabacak et al, 2014;Kim et al, 2017;Oliveria and Balaban, 2006;Rubio et al, 2016). However, in this study, the color change of dog cadavers that is preferred for education material in anatomy was estimated.…”
Section: Introductionmentioning
confidence: 83%